Al Qaṣāidu assyahīratu Li Tarqiyati Mahārat al Istimā’: Dirāsah Tajrībiyyah Qabliyyah bi Ma’hadi Tājil ‘Alawiyyīn - Baharun, Segaf; Maturedy, Faris; Haddad, Faishol (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2023)
The students’ drawbacks in listening skill, at the Ma’had Tajul Alawiyyin, has become a problem that must be solved, as it is a fundamental and significant skill in learning the Arabic language. This study aims to find out whether the implementation of al qasaid as syahirah in the book Maslak Al-Nabil can improve the listening skill or not at the Tajul Alawiyyin islamic boarding school. This research is important as it is that one of the method that can be used to overcome the students’ weaknesses in identifying the difference between the sounds of the audible letters, the sounds of similar letters, and understanding Arabic vocabulary] As for the research methods, it used the quantitative research method which focuses in finding out the effectiveness of teaching listening skill through the famous al qasaid as syahirah. The data was analyzed by using (t-Test). After the treatment, the researchers concluded that the use of al qasaid as syahirah is effective to improve students’ listening skill from the results obtained within the experimental group in the pre- and post-test which suggested that the mean score is significantly different with the control class. Therefore, the implementation of al qasaid as syahirah gives a significant effect for teaching and learning process of the Arabic listening skill.